The Reconstruction Method of Hodayot Manuscripts - Philip Suciadi Chia; Juanda Juanda (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2019)
Hodayot, in Hebrew means thanksgiving Psalms, is a collection of approximately thirty poems that give thanks to God. Hodayot is an important resource for understanding the piety and religious devotion of those who composed and recited them.In reconstructing of the original scroll, uses direct joins method, vertical alignment of material, horizontal alignment of material, and placement of fragments according to the Scribal Hands.The benefits of this reconstruction: Firstly, the accurate placing of adjacent fragments has enabled more portions of meaningful text to be recovered. Secondly, this method allows the original length of the scroll to be estimated as twenty-seven or twenty-eight columns of forty-one to forty-two lines each. The average length of lines is also known. Thirdly, it is now possible to investigate the overall structure of the collection, particularly when the data from the Cave 4 manuscripts is also considered. This group contains all of the compositions identified as Teacher Hymns and it strengthens the argument that they represent a distinct group by a single author.